The Relationship Between BMI and Spermogram Indices in Male Iranians Aged 20 to 50 Years Old - Zare-Mirzaie, Ali; Soltani Shirazi, Fazele; Moradi, Afshin; Vejdani, Zahra; Haghi Ashtiani, Mohammad Taghi; Kazeminezhad, Behrang (Archives of Men’s Health, 2018)
Introduction: Male factor infertility is the cause of 20 to 30% of infertile couples in population, and there are reports that obesity in men may be one of the factors affecting fertility. Accordingly, this study aimed to examine the relationship between Body Mass Index (BMI) and semen parameters in 20 to 50 year-old Iranian men. Materials and Methods: The archives of two major laboratories in Tehran were screened and the results of semen analyses from 640 nonvasectomized men referring during 2009-2013 were collected. Data on height, weight, BMI, age, sperm count, percentage of sperm motility, normal sperm morphology, and sperm viability was recorded. Anal-ysis of these data was performed using SPSS software. Results: The mean age of subjects and their mean BMI were 30.2 ± 5.9 years and 26.0 ± 4.1 kg/m2, respectively. The average values of semen parameters were as follows: total sperm count = 53.7 ± 33.6 million, pH = 8.2 ± 0.3, normal sperm morphology = 50.1 ± 10.9%, viability = 69.46 ± 12.6%, and grade-A sperms = 39.4 ± 16.8%. BMI had no significant correlation with the semen parameters including sperm morphology, viability, pH, and motility. Conclusion: No significant correlation between BMI and semen parameters was observed in the sample of Iranian males evaluated in this study.